DESKRIPSI KARAKTERISTIK, KEMAMPUAN ADAPTASI DAN PERKEMBANGAN INTEGRITAS DIRI LANSIA DI KELURAHAN RAWABUNGA, JAKARTA TIMUR - Sri Laela; Suryani Hartati (Institut Kesehatan Hermina, 2024)
Abstract Adaptation is a form of healthy response to stress and as an improvement in homeostasis in the internal environmental system. Changes that occur during the development of the elderly are stressors for the elderly and require adaptation to complete their developmental tasks. Psychosocial development that occurs around the age of 60 and above, there is a conflict between Integrity vs. Despair. The aim of this research is to determine the adaptive capacity and development of self-integrity of elderly people in Rawabunga Village, East Jakarta. The research method used was cross sectional. The sample in this study was 27 elderly people. This research was conducted in January - June 2023. The questionnaire used was a sheet measuring the development of personal integrity and a sheet measuring adaptability used by (Guslinda, 2011). The results of the research show that the elderly's ability to adapt to all aspects of change is quite good and the average development of the elderly's self-integrity is good. It is hoped that the elderly will have the ability to adapt and develop good personal integrity, in order to avoid psychosocial problems of despair with the characteristics of behavioral deviations, such as: not having appropriate self-esteem, criticizing/regretting the life they have lived, feeling lost, having no meaning in life, still wanting doing more but feeling afraid of not having enough time, blaming yourself, others and the environment, isolating yourself and not accepting the arrival of death. Key words: adaptation, personal integrity, elderly